2011
DOI: 10.1080/07391102.2011.10508599
|View full text |Cite
|
Sign up to set email alerts
|

Alpha7 Helix Plays an Important Role in the Conformational Stability of PTP1B

Abstract: The C-terminus of Protein Tyrosine Phosphatase 1B (PTP1B) includes an α-helix α7), which forms an allosteric binding site 20 å away from the active site. This helix is specific to PTP1B and its truncation decreases the catalytic activity significantly. Here, molecular dynamics (MD) simulations in the presence and absence of α7 were performed to investigate the role played by α7. The highly mobile α7 was found to maintain its contacts with loop 11 (L11)α3 helix throughout the simulations. The interactions of Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 98 publications
1
32
0
Order By: Relevance
“…In our simulation of the apo PTP1B, the three components maintained the triangular frame without allosteric site (Figure 4C), where the N-terminal helix α3 firmly coupled with loop 11 and helix α7 by the dynamical interactions among Tyr152, Tyr153, Ser190, Asn193, Gln288, Ser295 and Glu297. Olmez et al suggested that the stabilization of this structural feature through intensive interactions was closely associated with the physiological conformation of the WPD loop in yersina PTP and PTPL1 [24], and the missing of helix α7 in truncated PTP1B in modeling proposed the significant reduction in the flexibility of the catalytic WPD loop [24]. Consistent with above proposals, our MD simulations showed that upon the binding of compound- 3 , the intrinsic interactions among the triangular interactional region were disrupted and rearranged.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In our simulation of the apo PTP1B, the three components maintained the triangular frame without allosteric site (Figure 4C), where the N-terminal helix α3 firmly coupled with loop 11 and helix α7 by the dynamical interactions among Tyr152, Tyr153, Ser190, Asn193, Gln288, Ser295 and Glu297. Olmez et al suggested that the stabilization of this structural feature through intensive interactions was closely associated with the physiological conformation of the WPD loop in yersina PTP and PTPL1 [24], and the missing of helix α7 in truncated PTP1B in modeling proposed the significant reduction in the flexibility of the catalytic WPD loop [24]. Consistent with above proposals, our MD simulations showed that upon the binding of compound- 3 , the intrinsic interactions among the triangular interactional region were disrupted and rearranged.…”
Section: Resultssupporting
confidence: 89%
“…This finding indicated that the information exchange between helix α7 and C4 community in the allosteric compound- 3 bound state disappeared, with helix α7 departing from the core protein. The betweeness connecting helix α7 with C4 community includes the interactions from the hydrophobic WPD loop environment [19] as well as the triangular interactional region composed of the N-terminal helix α3, helix α7 and loop 11 [24]. Thus, these interactions could contain an allosteric pathway from helix α7 in the allosteric site to the WPD loop in the catalytic site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When benzofuran compounds bind this pocket, the activity of PTP1B is potently inhibited. Although initial molecular dynamics (MD) studies suggested that truncating and/or mutating helix α7 affects WPD loop closure (Li et al, 2014; Olmez and Alakent, 2011; Shinde and Sobhia, 2013), there is still no molecular model that explains how perturbations from the allosteric site are propagated to the active site. Furthermore, the role of dynamics and/or conformational changes in this process remain essential, open questions.…”
Section: Introductionmentioning
confidence: 99%
“…The target structure in TMD 1 simulation was altered between WPD open and WPD closed structures at 2.5 ns intervals, thus the frequency of the targeting function ( f 0 ) was 0.2 ns −1 (Figure 1A). The highly mobile region comprising residues 281 to 298 (α7 and the loop connecting α6 and α7) was not included in the structural analyses because of the disordered nature of this region [44], [52]. Aligning the C α atoms of Glu2 to Ala278, RMSD from the crystal structure of PTP1B leveled off between 1.5 and 2.0 Å, showing that protein structure was maintained in both simulations (Figure S2A).…”
Section: Resultsmentioning
confidence: 99%